Strategies of Youth Anti-Drug Activists in Promoting National Drug Prevention Programs to Mitigate Substance Abuse Among Influencers - Arif Hidayat; Nurul Hasfi (Warta Ikatan Sarjana Komunikasi Indonesia, 2024)
The purpose of this study is to ascertain the tactics, chances, and difficulties that the Bengkulu City National Narcotics Board has faced when educating the younger generation (Gen Z) about P4GN. The concept of the Berlo SMCR communication model is employed in this study's descriptive qualitative analysis to describe the tactics, possibilities, and difficulties faced by PUPAN Bengkulu in spreading P4GN information. The study's informants were chosen using the snowball sampling approach. Techniques for gathering data included recordkeeping, interviews, and observation. The strategies employed in data analysis include data reduction, data visualisation, and conclusion drawing. PUPAN Bengkulu uses a communication strategy that is carried out through the creation of strategic plans, their implementation, evaluation, and management. Prior to distributing P4GN material, PUPAN Bengkulu first identifies and selects the resource person. It next ascertains the intended recipient of the P4GN material and composes the message in accordance with the recipient. The media and communication channels that PUPAN Bengkulu uses to spread P4GN information are selected based on the kind of media that the general public accesses most frequently. PUPAN Bengkulu has a number of obstacles, including a shortage of manpower, inadequate facilities and infrastructure, geographic limitations, and difficulties mobilising large numbers of people during the epidemic.